Knockdown of Atg7 suppresses Tumorigenesis in a murine model of liver cancer - Cho, Kyung Joo (Transl Oncol, 2021)
Hepatocellular Carcinoma (HCC) is the most common type of primary liver cancer in adults and a leading cause of cancer-related deaths worldwide. Studies have shown that autophagy is significantly involved in carcinogenesis, in particular, driven by activated RAS signaling. Autophagy related 7 (Atg7) is a critical component for the formation of autophagosome and required for autophagy processes. We investigated the role of autophagy in RAS-driven tumorigenesis in the liver, via the knockdown of Atg7 in the model. Transposon vectors encoding short hairpin RNAs targeting Atg7 (Atg7 shRNA) were constructed. Inhibition of autophagy via Atg7 knockdown was tested in Hep3B cells cultured in nutrient-starved medium. Formation of autophagosome was suppressed in nutrient-starved Hep3B cells expressing Atg7 shRNA, demonstrating that it efficiently inhibited autophagy in HCC cells. Transposons encoding Atg7 shRNA were mixed with those expressing HRAS(G12V) and p53 shRNA, and subsequently used for hydrodynamic injection to 5-week-old C57BL/6 mice. Tumorigenesis in livers induced by HRAS(G12V) and p53 shRNA was significantly suppressed by Atg7 knockdown. The inhibition of autophagy led to a decreased proliferation of cancer cells, as determined by Ki-67 staining. Our data indicate that knockdown of Atg7 led to a significant decrease in tumorigenesis in a murine HCC model induced by activated RAS. Inhibition of autophagosome formation is expected to be a therapeutic option for liver cancer.